Faktor-faktor yang berhubungan dengan kejadian carpal tunnel syndrome (CTS) pada pegawai badan perencanaan pembangunan daerah (BAPPEDA) - Elsa Putri; Budi Aswin; Adelina Fitri; Usi Lanita (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Abstract   Background: Public sector employees often face high work demands, particularly in computer-based tasks. One of the health problems commonly associated with these activities is Carpal Tunnel Syndrome (CTS). Badan Perencanaan Pembangunan Daerah (BAPPEDA) is a regional technical institution responsible for regional development planning, involving intensive administrative activities such as data processing, report preparation, and virtual meetings, which often require computer use for 4–8 hours per day. Purpose: to analyze the factors associated with the occurrence of Carpal Tunnel Syndrome (CTS) among employees of Badan Perencanaan Pembangunan Daerah (BAPPEDA). Method: This study employed a quantitative approach with a cross-sectional design. The sample consisted of 75 employees selected using a total sampling technique. Data were collected through questionnaires and observations, then analyzed using univariate and bivariate analysis with the Chi-Square test. Results: The majority of respondents reported CTS complaints (72%). The results showed significant relationships between age (p=0.000), gender (p=0.005), work period (p=0.000), and repetitive movements (p=0.002) with the occurrence of Carpal Tunnel Syndrome (CTS) among employees of Badan Perencanaan Pembangunan Daerah (BAPPEDA). Meanwhile, medical history (p=0.097) and body mass index (BMI) (p=0.697) did not show significant relationships with the occurrence of CTS. Conclusion: Age, gender, work period, and repetitive movements were significantly associated with the occurrence of Carpal Tunnel Syndrome (CTS) among employees of Badan Perencanaan Pembangunan Daerah (BAPPEDA). In contrast, medical history and body mass index (BMI) were not significantly associated with CTS.   Keywords: Age; Bappeda Employees; Carpal Tunnel Syndrome; Gender; Repetitive Motion; Risk Factors; Work Duration.